Root cause analysis of inlet connector leakage problem in fuel injection pump by Shainin methodology. (2020) - Pankaj, Jijil; Kumar, Sumeet; Deepak, D.
Abstract: Quality engineering is popularly adopted by manufacturing industry and the problem solving is an important part of quality engineering. One such problem solving technique is explained in this study. This study mainly focuses on finding the root cause of rejection due to leakage in the inlet connector assembly in the fuel injection pumps. Shainin method is used mainly to converge to the root cause of the problem and propose a solution for quality improvement. Misalignment of the inlet connector with respect to the housing of the pump is identified as the root cause for the leakage caused. Hence this study explains converging to the root cause and validating the result by using the Shainin methodology.